3r-6(3r+6)=-66

Simple and best practice solution for 3r-6(3r+6)=-66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3r-6(3r+6)=-66 equation:



3r-6(3r+6)=-66
We move all terms to the left:
3r-6(3r+6)-(-66)=0
We add all the numbers together, and all the variables
3r-6(3r+6)+66=0
We multiply parentheses
3r-18r-36+66=0
We add all the numbers together, and all the variables
-15r+30=0
We move all terms containing r to the left, all other terms to the right
-15r=-30
r=-30/-15
r=+2

You can always share this solution

See similar equations:

| -6×=5x+22 | | 16=b=-4 | | x+1,1/2=2,1/4 | | m+6=7,3/8 | | Y=13/8x+-9 | | 75x=65x+25 | | 12x-3x+84=12x+42 | | 1,2/3+x=5 | | 2x+(x/12)=180 | | X/3+5x=x26 | | b=14-b | | 10x-5x+150=10x+100 | | 12b^2-15b=3b() | | -1=n/4=3 | | -2z-6z=4/3 | | 2x-1+3x=15 | | 2x-1+3x=18 | | (5x+11)=1/2(16x-26) | | v/5+6.3=-6.2 | | 5x+11=16x-26/2 | | 5x+11=1/216x-26 | | (3x-7)(x+11)=588 | | 3y+15=62 | | 5x+11=16x-20/2 | | 5x+11=1/216x-20 | | x/10-9=-9 | | 28=u/5+16 | | 16t^2-29t+7=17 | | -5a/3=30 | | 5x+38=12-28 | | 16t^2-29t-10=0 | | 5x+8x-84=105-8x |

Equations solver categories